Study on Stress Aspects In Migraine: Exploring the Impact of Migraine on Work Productivity and Treatment Costs (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Some significant consequencesoccur for the wider community in terms of time lost from work and treatmentcosts due to headache. The headache disorder is mainly classified in two types-(i) primary headache disorders and (ii) secondary headache disorder. Primaryheadache disorders are again classified as migraine headache, tension-typeheadache and cluster headache. Migraine is a painful neurological condition andits symptoms are intense, throbbing and disabling episodic pain. Migraineheadaches are usually characterized by severe pain on one or both sides of thehead  and the pain usually last from 4 to72 hours duration and are often accompanied by hypersensitivity to light andsound and  feelings of nausea. It is acondition that has always plagued the human race.